ChemInform Abstract: Model Studies on Peroxidic Glutathione Transferase (GST) Inhibitors: C5‐Methylated 1, 2, 4‐Trioxanes with C6‐Acrylate Side Chains. Issue 47 (November 2015) - Griesbeck, Axel G.; Maassen, Andreas; Braeutigam, Maria; Pietsch, Markus
Abstract: The diastereoselective porphyrin‐sensitized singlet oxygen ene reaction of allylic alcohol (I) gives the key precursor (II), which can be easily converted into the title trioxane derivatives.